Case Report: “Stent-within-a-Stent” technique after telescopic flow diverter reconstruction for basilar artery aneurysm with proximal stenosis - Mammadinova, Iroda; Nurimanov, Chingiz; Nurakay, Nurtay; Menlibayeva, Karashash; Akshulakov, Serik; Makhambetov, Yerbol (Frontiers in Surgery, 2025)
BackgroundComplex basilar artery aneurysms are challenging to treat due to their deep anatomical location and proximity to critical perforating arteries, as well as their frequent fusiform morphology and association with long-segment stenosis or atherosclerotic changes. Endovascular flow diversion has become an important option; however, its use in large and fusiform basilar artery aneurysms is complicated by the risks of device malapposition, migration, and incomplete occlusion.Case presentationWe report a case of a large basilar artery aneurysm with severe pre-aneurysmal stenosis treated using a telescopic flow-diverter strategy. Balloon angioplasty prior to stent deployment was performed to optimize vessel diameter, followed by the sequential distal-to- proximal placement of overlapping flow diverters. Post-procedural angiography revealed device instability, necessitating the deployment of an additional flow diverter in a “stent-within-a-stent” configuration to improve wall apposition and prevent migration. This approach resulted in sustained aneurysm thrombosis and long-term vessel patency.ConclusionThis case illustrates the technical challenges of managing complex basilar artery aneurysms and emphasizes the role of adjunctive stenting in stabilizing flow diverters. Carefully individualized endovascular strategies that account for fusiform morphology, long-segment arterial involvement, atherosclerotic changes, and the perforator-rich environment, together with technical challenges such as the need for telescopic reconstruction or adjunctive balloon angioplasty, are essential for enhancing procedural safety and achieving durable aneurysm occlusion in high-risk patients.